2023
DOI: 10.29103/micoms.v3i.193
|View full text |Cite
|
Sign up to set email alerts
|

Description of Mercury Poison Clinical Symptoms in Workers and Communities Around the Small-Scale Gold Processing Area

Abstract: The traditional gold processing process in Paya Seumantok Village, Krueng Sabee District, Aceh Jaya Regency, Aceh Province, is carried out using the amalgamation method which still uses mercury in the process, so it poses a risk to the health of workers and the surrounding community. This study aims to obtain an overview of the clinical symptoms experienced by workers and the community around the gold processing area. This study uses qualitative research methods with the number of community respondents were 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…It is widely used in the gold mining process which serves to purify precious metals. Gold processing with amalgamation techniques is known to damage the environment and pose human health risks (Kamil & Karma, 2022). Mercury problems to the environment in Indonesia mostly come from artisanal small-scale gold mining, also known as PETI (unlicensed gold mining).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely used in the gold mining process which serves to purify precious metals. Gold processing with amalgamation techniques is known to damage the environment and pose human health risks (Kamil & Karma, 2022). Mercury problems to the environment in Indonesia mostly come from artisanal small-scale gold mining, also known as PETI (unlicensed gold mining).…”
Section: Introductionmentioning
confidence: 99%
“…According to research (Lensoni et al, 2022) in his research showed that the most acute clinical symptoms experienced by respondents in the gold mining area were coughing (8 respondents), and pelvic pain, diarrhea, abdominal pain, vomiting, nausea, and headaches experienced by 7 respondents. While chronic clinical symptoms workers experience headaches and insomnia (8 respondents), irritability (6 respondents), anxiety (6 respondents), cramps (5 respondents), and trembling (4 respondents) (Kamil & Karma, 2022)…”
Section: Introductionmentioning
confidence: 99%